Association between breastfeeding and osteoporotic hip fracture in women: a dose-response meta-analysis - Xiao, Haixiang (J Orthop Surg Res, 2020)
OBJECTIVE: Approximately 300 mg of calcium a day is provided into infants to maintain the physical development of infants, and 5 to 10% bone loss occurs in women during breastfeeding. Hip fractures are considered the most serious type of osteoporotic fracture. We performed this meta-analysis to investigate the association between breastfeeding and osteoporotic hip fractures. MATERIAL AND METHODS: PubMed and Embase were searched until May 1, 2019, for studies evaluating the relationship between breastfeeding and osteoporotic hip fracture in women. The quality of the included studies was evaluated by the methodological index for non-randomized studies (MINORS). For the dose-response meta-analysis, we used the “generalized least squares for trend estimation” method proposed by Greenland and Longnecker to take into account the correlation with the log RR estimates across the duration of breastfeeding. RESULTS: Seven studies were moderate or high quality, enrolling a total of 103,898 subjects. The pooled outcomes suggested that breastfeeding can decrease the incidence of osteoporotic hip fracture (RR = 0.64 (95% CI 0.43, 0.95), P = 0.027). Dose-response analysis demonstrated that the incidence of osteoporotic hip fracture decreased with the increase of breastfeeding time. The RR and 95% CI for 3 months, 6 months, 12 months, and 24 months were RR = 0.93, 95% CI 0.88, 0.98; RR = 0.87, 95% CI 0.79, 0.96; RR = 0.79, 95% CI 0.67, 0.92; and RR = 0.76, 95% CI 0.59, 0.98, respectively, whereas no significant relationship was found between them when the duration of breastfeeding time was more than 25 months. CONCLUSIONS: Our meta-analysis demonstrated that the incidence of osteoporotic hip fracture decreased with the extension of breastfeeding time. However, there is no significant relationship between them when the duration of breastfeeding time was more than 25 months.